Incidence of Heterotopic Ossification after Surface and Conventional Total Hip Arthroplasty: A Comparative Study Using Anterolateral Approach and Indomethacin Prophylaxis. (24th June 2013) - Regis, Dario; Sandri, Andrea; Sambugaro, Elena
Abstract : The incidence and severity of heterotopic ossification (HO) in two homogeneous groups of patients that received surface replacement arthroplasty (SRA) and conventional total hip arthroplasty (THA) were evaluated retrospectively. Thirty-nine patients undergoing 42 hip resurfacing procedures and 41 primary cementless THAs through an anterolateral approach received a 10-day course of 150 mg/die of indomethacin postoperatively. The median surgical time was 190 minutes and 156 minutes, respectively (P < 0.003 ). At a minimum 1-year followup, the development of HO was assessed on standard X-ray using Brooker grading. Ectopic bone formation was detected in five cases (11.9%, two Brooker grade I and three grade II) in the SRA group and in 14 hips (34.1%, 12 grade I and two grade II) treated with conventional THA, but the difference was not significant (P < 0.11 ). No clinically relevant periprosthetic ossification (Brooker III or IV) occurred in both groups. Although the difference was not statistically significant, the incidence of HO after SRA was lower than conventional THA. More extensive soft tissue trauma, bone debris, and longer operative time in hip resurfacing are not likely to be absolute risk factors for HO. Further investigations including larger patient populations are needed to confirm these findings.